Dynamic Characteristics Analysis of an Assembly Robot for a Wine Box Base Considering Radial and Axial Clearances in a 3D Revolute Joint - Yuan Wang; Ruiqin Li; Juan Liu; Zengyu Jia; Hailong Liang (Applied Sciences, 2023)
Precisely fitting the bottom sticker of the wine box base to the base model with glue is an important process of the wine box base production line. The influence of joint clearance in the assembly robot on the assembly precision of wine box bases is investigated. We analyze the axial clearance and radial clearance in a 3D revolute joint of the assembly robot and present 12 possible contact forms between bearings and journals, as well as three modes of free flight mode, continuous contact mode, and pseudo penetration mode between them under the different contact forms. The contact force models of normal and tangential force between bearings and journals are established using the Lankarani–Nikravesh contact model and modified Coulomb friction law, respectively. Taking the joint clearance of one joint of the wine box base assembly robot as an example, the dynamic equations of the joint with clearance are established, and the dynamic characteristics of the robot caused by the joint clearance are analyzed. The results show that, the larger the clearance, the more easily the dynamic characteristics of the robot end effector are influenced.